Forgiveness pada remaja korban perceraian orang tua: Menguji peran penerimaan diri - Rachma, Adhelia; IGAA Noviekayati; Amherstia Pasca Rina (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to determine the relationship between self-acceptance and forgiveness in adolescents who experience divorce from their parents in Surabaya. The hypothesis proposed is that there is a relationship between self-acceptance and forgiveness for adolescents who experience divorce from their parents. This research is a quantitative study with a total of 88 adolescents as respondents. The instrument used in this research is the forgiveness scale and self-acceptance scale. The data analysis technique used is product-moment correlation by using the data collection method in the form of a questionnaire and distributed via Google form using a Likert scale. The data obtained shows that there is a significant positive correlation between self-acceptance and forgiveness. The score rxy = 0.266 with p = 0.012 (p <0.05) was obtained. The result, the higher the self-acceptance, the higher the attitude of forgiveness in adolescents. Keywords: Self-acceptance; Forgiveness